A new coumarin from stem bark of Calophyllum wallichianum. Issue 21 (2nd November 2018) - Tee, Keng Hong; Ee, Gwendoline Cheng Lian; Ismail, Intan Safinar; Karunakaran, Thiruventhan; Teh, Soek Sin; Jong, Vivien Yi Mian; Mohd Nor, Siti Mariam
Abstract: A phytochemical study carried out on the plant, Calophyllum wallichianum has led to the isolation of a new coumarin, wallimarin T (1 ) and a known coumarin, calanolide E (2 ) along with two common triterpenes, friedelin (3 ) and stigmasterol (4 ). The structures of these compounds were elucidated with the aid of spectroscopic analyses such as FT-IR, GC-MS, and NMR. MIC assay against the Bacillus bacteria were conducted on the extracts and this gave MIC values ranging from 0.313 to 1.25 mg/mL. Compound2 was weakly inhibitory towards the Bacilli strains with MIC values ranging from 0.25–0.50 mg/mL. Wallimarin T(1) was not active towards all four bacteria. Overall, the extracts exhibited weak bactericidal properties whereas compound2 was not bactericidal on the tested bacteria. The hexane and chloroform extracts of the plant were found to be inhibitors to the growth of Bacillus megaterium, Bacillus cereus, Bacillus pumilus and Bacillus subtilis . Abstract :